Assessing the Best Practices in Media and Communication Training - Mutunga, Isaac Mutwiri (Jurnal Komunikasi Islam, 2015)
This article tries to assess how Media and Com–munication training in Kenya has adapted to the changes in the industry based on a mixed methods study. The article argues that universities are trying to adapt their media and communication curricula to the converged media landscape by adding ‘new media’ units that try to address the changes in the industry. They have maintained specializations (Broadcast, print, film) but none has a general programme that equips students with skills to work across media. There is a divergent view between practice and academy on the extent. This is because their perspectives on MCS education and not what is on the ground. Therefore, there is need to bridge the gap between the two by constantly engaging in team teaching, workshops, internships and co-productions.